When do epidemics end? scientific insights from mathematical modelling studies - Linton, NM; Lovell-Read, F; Southall, E; Lee, H; Akhmetzhanov, AR; Thompson, RN; Nishiura, H (Tech Science Press, 2022)
Quantitative assessments of when infectious disease outbreaks end are crucial, as resources targeted towards outbreak response typically remain in place until outbreaks are declared over. Recent improvements and innovations in mathematical approaches for determining when outbreaks end provide public health authorities with more confidence when making end-of-outbreak declarations. Although quantitative analyses of outbreaks have a long history, complex mathematical and statistical methodologies for analysing outbreak data were developed early in the twentieth century and continue to be refined. Historically, such methodologies focused primarily on factors affecting the early and middle phases of an outbreak, with less attention given to determining how and when outbreaks end. This review discusses mathematical modelling methods from the last 20 years that have been developed for determining the ends of infectious disease outbreaks, and consider the factors that affect the accuracy of such determinations. When surveillance systems provide timely and representative data to inform models, the timings of end-of-outbreak declarations can be fine-tuned to allow outbreaks to be declared over quickly and with a low risk of being incorrect. Premature declarations that outbreaks are over may undermine earlier achievements in disease control and may result in a resurgence of cases, but unnecessary delays in declaring outbreaks over cause significant economic and social harms. Appropriate declarations that balance the benefits of releasing control measures against the risk of a surge in cases thereby allow public health resources to be conserved (and economic and social pressures to be reduced) while limiting the potential for additional transmission